Estimation of Immunoglobulins and complement component C3 and C4 in some patients with Hodgkin and Non-Hodgkin Lymphoma in Basrah Governorate - Jawad Kadhim AlAli, Shereen (University of Thi-Qar Journal of Science, 2010)
The humoral immune response including serum Immunoglobulins (IgG, IgM and IgA) and complement components (C3 and C4) level in Hodgkin (HL) and Non-Hodgkin(NHL) Lymphoma patients were studied. Forty five samples were taken (20 NHL ,10 HL , 15 control) , examined by single Radial Immunodiffusion assay (SRID).The results showed a non significant elevation of IgG level in the sera of HL & NHL patients 1097.9 mg/dl and 1088.3 mg/dl , respectively , in comparison with control group ( 950.7 mg/dl ) ; Non significant elevation of IgM level also had been reported in the sera of HL & NHL patients 232.71 mg/dl and 228.6 mg/dl , respectively , while it reached 166.78 mg/dl in control group. The results revealed a non significant decrease in IgA level in the sera of HL patients (227.2 mg/dl) while NHL patients showed non significant elevation of it ( 324.1 mg/dl) while it reached 304.3 mg/dl in control group. There was a non significant decrease in complement component C4 level in the sera of HL patients 21.331 mg/dl while NHL patients showed non significant and slightly increase of it ( 25.565 mg/dl ) in comparison with the mean value of the control group which reached 24.95 mg/dl. complement component C3 level was non significantly increase in the sera of HL patients 141.98 mg/dl while NHL patients showed non significant decrease in complement component C3 level 116.66 mg/dl in comparison with the mean value of the control group which reached 124.01 mg/dl.